The Effect of Self Modeling Videos on The Ability To Brush Teeth In Children With Autism Spectrum Disorders at Bina Anggita Autism Special School Yogyakarta - Rizqi, Amanullah; Siti, Hidayati; Gina, Apriana (Jurnal Ners, 2024)
The limitations experienced by children with autism make them unable to brush their teeth properly and correctly. Video self modeling (VSM) can be applied as an alternative therapy in training skills in children with autism. This study aims to analyze the effect of VSM on the ability to brush teeth in children with autism at the Bina Anggita Special School for Autism Yogyakarta. This study used an experimental research design with a single subject experimental design, a sample of ten people. The intervention provided was in the form of VSM about brushing teeth. Data were collected through before and after intervention and maintenance using brushing observation sheets. The purpose of the study was to analyze the effect of Video Self Modeling on the ability to brush teeth in children with Autism Spectrum Disorders. This Research can be used as additional reference material and reading for dental health studies for additional knowledge and basis for conducting further research. This research also supports the sixth pillar of health transformation, namely the transformation of health technology with the use of self-modeling videos. This study uses experimental research design with a single subject experimental design approach. The population and sample of this study were children who attended the Bina Anggita Special School for Autism Yogyakarta as many as 69 children The sample of this study was 10 children. The sampling technique used in this study was random sampling with purposive sampling. Purposive sampling is based on certain considerations made by the researchers themselves, based on previously known characteristics or characteristics of the population. The dependent variable in this study is the ability to brush teeth in children with autism. While the independent variable is the intervention or treatment given, namely learning through self-modeling video techniques. The path of this research is: There are several phases in this study, namely baseline-1 phase (A1), intervening phase (B2), baseline-2 phase (A2). This research activity has been carried out at the Bina Anggita Special School for Autism Yogyakarta from July to October 2023. Research Results Results before the intervention showed that children had the inability to brush their teeth properly (x ?=54.67%), after the intervention children experienced an increase (x ?=62.67%). The results of child maintenance have a sedentary ability to brush their teeth (x ?=73.00%). There is an effect of VSM on the ability to brush teeth in children with autism. It is recommended to use Self Modeling Videos in teaching other skills such as toilet training, personal hygiene. Keywords: Autism, Brushing Teeth, Self Modeling Videos